Advances in accounting education teaching and curriculum innovations. Vol. 15 - Feldmann, Dorothy; Rupert, Timothy J. (Emerald, 2014)
Advances in accounting education : teaching and curriculum innovations investigates how teaching methods or curricula/programs in accounting can be improved. Volume 15 includes papers examining communication apprehension, self-directed learning in managerial accounting courses, and a section on integrating accounting with other business disciplines.
Keywords: Accounting -- Study and teaching.; Educational innovations.; elektronické knihy; electronic books